Administration Of Justice Under The Shariah, Common Law And Civil Law System: Towards A Better Understanding - A. Baderin, M. (Universiti Sains Islam Malaysia, 2024)
There is today a general perception that the traditional differences between the Common Law and Civil Law systems have shrunk greatly and that both, being secular “Western” systems, should be able to accommodate one another and impact on one another easily and positively. It is the Shar_‘ah system, being based on divine law, that is often perceived as being radically different and possibly not having anything in common with either the Common Law or the Civil Law systems respectively. Our analysis of administration of justice in this paper however demonstrates that the jurisprudence of the three legal systems have evolved along similar lines and that under each of the systems the relevant theories and principles of administration of justice have been influenced by reasonableness and expediency which gives room for the necessary flexibility to ensure the realisation of substantive justice under each one of the three legal systems, if there is the political and judicial will to do so on the part of the ruling authority, the judiciary and other relevant institutions of administration of justice respectively. In view of the continuing interaction between the three legal systems in different countries of the world today, there is a need to continue promoting a better understanding of the systems to enhance an effective administration of justice across the legal systems globally.